Dietary Medium-Chain Triglyceride Decanoate Affects Glucose Homeostasis Through GPR84-Mediated GLP-1 Secretion in Mice - Nonaka, Hazuki; Ohue-Kitano, Ryuji; Masujima, Yuki; Igarashi, Miki; Kimura, Ikuo (Frontiers in Nutrition, 2022)
Background: Dietary triglycerides are an important energy source; however, their excess intake causes metabolic diseases such as obesity and type 2 diabetes. Medium-chain triglycerides (MCTs) as triglyceride forms of medium-chain fatty acids (MCFAs) are applied to meet the energy demands of athletes, the elderly, and people with stunted growth, because MCFAs are efficiently converted into energy for immediate utilization by the organs and do not accumulate as fat. Although the intake of each MCT type (octanoate; C8:0, decanoate; C10:0, and dodecanoate; C12:0) exhibits beneficial metabolic effects, individual functional differences remain unclear. Methods: MCTs or MCFAs were administrated to male GPR84-deficient mice with a C57BL/6J background and mouse enteroendocrine cell line STC-1, and the effects on glucose homeostasis and gut hormone GLP-1 secretion were evaluated. Results: C10:0 intake improves glucose metabolism through the MCFA receptor GPR84-mediated GLP-1 secretion. Each MCT intake showed resistance to obesity and improved metabolic parameters compared with lard intake. Moreover, oral administration of MCTs enhanced glucose tolerance, especially C10:0 administration, which sufficiently increased plasma GLP-1 levels. Additionally, C10:0 stimulation promoted GLP-1 secretion via GPR84 in STC-1, enhanced glucose tolerance through GPR84-mediated GLP-1 secretion, and showed resistance to high-fat diet (HFD)-induced obesity in mice. Conclusions: Dietary MCT (C10:0) intake efficiently may protect against obesity and improve insulin resistance via GLP-1 secretion.